Attitudes of young customers towards activities promoting electronic banking - Tomczyk, Kamila (Postawy młodych klientów wobec działań promujących bankowość elektroniczną, 2020)
Learning about the behaviour and factors influencing the attitudes of young customers towards activities promoting electronic banking constitutes a key factor determining the effective acquiring of such customers. The presented results of the author’s own research conducted among young customers confirm that promotional activities should include contents personalised for this age group and primarily the use of social media as communication channels
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 2 (56), s. 63-73
Keywords: electronic banking; customer attitudes; generation Z; promotional activities; bankowość elektroniczna; postawy klientów; pokolenie Z; działania promocyjne